Preventing Postoperative Healthcare Associated Infections: The Experience of Two European Cardiac Surgery Intensive Care Units - Elisabetta Palma; Alfia Lizzi; Alessia Marini (Archives of Nursing Practice and Care - Peertechz Publications, 2015)
Aims: to investigate the relationship between nursing workloads (first shift) and Healthcareassociated Infections (HAI) in two European Cardiac Surgery Intensive Care Units (ICUs). Background: Critically ill patients may develop an infection, because of their clinical condition, and the invasive interventions received. Inadequate nursing workloads may increase the risk of HAIs. Design: observational study in two European ICUs (Spain and Italy) Methods: in the period February-June 2010 we assessed 60 patients per ICU using the Simplified Acute Physiology Score II (SAPS II) and the Nine Equivalents of Nursing Manpower Score (NEMS). Results/Findings: the two ICUs have similar SAPS II and NEMS scores, however the distribution of nurses activities is different. The time spent in HAIs surveillance activities is greater in the Spanish ICU (155 minutes over 340) than in the Italian ICU (45 minutes over 320). Conclusion: in the Spanish ICU, the presence of RN assistants allows nurses to spend more time in activities of NI prevention This could probably encourage the observance of safety rules such as evidence-based aseptic work practices.